Application of the transgenic pig model in biomedical research: A review - Wei, Jialin; Zhang, Wen; Li, Jie; Jin, Ye; Qiu, Zhidong (Frontiers in Cell and Developmental Biology, 2022)
The large animal model has gradually become an essential part of preclinical research studies, relating to exploring the disease pathological mechanism, genic function, pharmacy, and other subjects. Although the mouse model has already been widely accepted in clinical experiments, the need for finding an animal model with high similarity compared with a human model is urgent due to the different body functions and systems between mice and humans. The pig is an optimal choice for replacement. Therefore, enhancing the production of pigs used for models is an important part of the large animal model as well. Transgenic pigs show superiority in pig model creation because of the progress in genetic engineering. Successful cases of transgenic pig models occur in the clinical field of metabolic diseases, neurodegenerative diseases, and genetic diseases. In addition, the choice of pig breed influences the effort and efficiency of reproduction, and the mini pig has relative obvious advantages in pig model production. Indeed, pig models in these diseases provide great value in studies of their causes and treatments, especially at the genetic level. This review briefly outlines the method used to create transgenic pigs and species of producing transgenic pigs and provides an overview of their applications on different diseases and limitations for present pig model developments.